2016
DOI: 10.1002/jcp.25380
|View full text |Cite
|
Sign up to set email alerts
|

l‐glutamine Improves Skeletal Muscle Cell Differentiation and Prevents Myotube Atrophy After Cytokine (TNF‐α) Stress Via Reduced p38 MAPK Signal Transduction

Abstract: Girven, M, Dugdale, HF, Owens, DJ, Hughes, DC, Stewart, CE and Sharples, AP L-glutamine improves skeletal muscle cell differentiation and prevents myotube atrophy after cytokine (TNF-α) stress via reduced p38 MAPK signal transduction http://researchonline.ljmu.ac.uk/3305/ Article LJMU has developed LJMU Research Online for users to access the research output of the University more effectively. Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 86 publications
1
33
1
Order By: Relevance
“…Cells were then seeded at 90,000 cells mL –1 in 2 mL of growth media [GM; 4.5 g L –1 glucose DMEM, which included 4 m m l ‐glutamine, 10% hiFBS, 10% hiNBCS, supplemented with an additional 2 m m l ‐glutamine (Girven et al . ), 100 U mL –1 penicillin, 100 µg mL –1 streptomycin, 0.5 mg mL –1 6‐aminocaproic acid, 50 µ m l ‐ascorbic acid, 50 µ m l ‐proline] onto each sylgard coated (Sylgard 184 Elastomer Kit; Dow Corning, Midland, MI, USA) 35 mm culture dish containing a pre‐polymerized (10 min at room temperature and 1 h at 37°C) fibrin gel. The fibrin gel was made up of 500 µL of thrombin‐solution (10 U mL –1 thrombin, 8 µL mL –1 aprotinin at 10 mg mL –1 ) and 200 µL of fibrinogen at 20 mg mL –1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were then seeded at 90,000 cells mL –1 in 2 mL of growth media [GM; 4.5 g L –1 glucose DMEM, which included 4 m m l ‐glutamine, 10% hiFBS, 10% hiNBCS, supplemented with an additional 2 m m l ‐glutamine (Girven et al . ), 100 U mL –1 penicillin, 100 µg mL –1 streptomycin, 0.5 mg mL –1 6‐aminocaproic acid, 50 µ m l ‐ascorbic acid, 50 µ m l ‐proline] onto each sylgard coated (Sylgard 184 Elastomer Kit; Dow Corning, Midland, MI, USA) 35 mm culture dish containing a pre‐polymerized (10 min at room temperature and 1 h at 37°C) fibrin gel. The fibrin gel was made up of 500 µL of thrombin‐solution (10 U mL –1 thrombin, 8 µL mL –1 aprotinin at 10 mg mL –1 ) and 200 µL of fibrinogen at 20 mg mL –1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, C2C12 cells were grown on T75 flasks to ß80% confluence. Cells were then seeded at 90,000 cells mL -1 in 2 mL of growth media [GM; 4.5 g L -1 glucose DMEM, which included 4 mM L-glutamine, 10% hiFBS, 10% hiNBCS, supplemented with an additional 2 mM L-glutamine (Girven et al 2016), 100 U mL -1 penicillin, 100 µg mL -1 streptomycin, 0.5 mg mL -1 6-aminocaproic acid, 50 µM L-ascorbic acid, 50 µM L-proline] onto each sylgard coated ( Figure 3. UBR5 gene expression and protein abundance after skeletal muscle atrophy and recovery following nerve crush injury A, muscle weight (mg) of the gastrocnemius/GSTC in mice after nerve crush injury (NCI) over a period of atrophy (3-14 days) and recovery (14-60 days) of muscle mass.…”
Section: Mechanical Loading Of Bioengineered Skeletal Muscle In Vitromentioning
confidence: 99%
“…Briefly, C2C12 cells were grown on T75's to approx. 80% confluence whereby 90,000 cells/ml in 2 ml growth media (GM; 4.5 g/l glucose DMEM that included 4 mM L-glutamine, 10% hiFBS, 10% hiNBCS, supplemented with an additional 2 mM L-glutamine (Girven et al, 2016),100 U/ml penicillin, 100 μ g/ml streptomycin, 0.5 mg/ml 6- 3.5% hiFBS/ 3.5% hiNBCS) maintenance media (MM) to promote myotube formation for a further 10 days.…”
Section: Mechanical Loading Of Bioengineered Skeletal Muscle In-vitromentioning
confidence: 99%
“…The physiological role of glutamine metabolism during embryonic development is not fully known [5], especially, considering the proliferation, differentiation and maturation of muscle tissue, the role of glutamine appears to be crucial. Undoubtedly, glutamine supports therapy reducing the degradation of muscle tissue, caused by inflammation, partly by satellite cell activation, especially after damaging exercise [6,7]. Interestingly, experiments with the C2C12 myoblasts' cell line, have shown that L-Glu improves skeletal muscle cell differentiation and prevents myotube atrophy after cytokine (TNF-α) via regulation of p38 MAPK [7].…”
Section: Introductionmentioning
confidence: 99%